Human parvovirus B19 in Iranian pregnant women: A serologic survey - Zakieh Rostamzadeh Khameneh; Haleh Hanifian; Razieh Barzegari; Nariman Sepehrvand (Indian Journal of Pathology and Microbiology, 2014)
Background: Parvovirus B19 infection is associated with clinical symptoms that vary in the spectrum from trivial to severe. The important clinical manifestations are erythema infectiosum or the fifth disease, transient aplastic anemia in patients with hemoglobinopathies, acute polyarthralgia syndrome in adults, hydrops fetalis, spontaneous abortion and stillbirth. Acute infection in nonimmune pregnant women can lead to fetal hydrops. In view of the many complications that can result from acute parvovirus B19 infections during pregnancy, documenting the seroprevalence of anti-parvovirus B19 IgG and its association with the history of abortion in an Iranian population of pregnant women would be of value. Materials and Methods: Serum samples from 86 pregnant women were collected between May and September 2011 in West Azerbaijan province of Iran. Every pregnant woman completed a questionnaire which included age, history of tattooing, blood transfusion, and abortion. Anti-B19 specific IgG was detected by using commercial enzyme-linked immunosorbent assays. Results: Anti-B19-specific IgG antibody was detected in (65/86, 75.6%) of pregnant women. The mean age was 25.56 ± 5.30 years and three women had a documented history of blood transfusion (2 of them tested seropositive for B19). 16/18 (88.8%) of women with a history of abortion were IgG positive. The frequency of abortion sessions in the seropositive group (25 sessions of abortion: 11 women experienced once, 2 twice, 2 thrice and one 4 times) was 4.03 times greater than abortion in seronegative group (2 abortions/21 seronegative women). Conclusion: Our study reaffirms previous reports regarding the higher frequency of abortion among anti-B19 IgG seropositive pregnant women and a possible role of this viral infection in the pathogenesis of abortion.